Assessment of physico-chemical parameters and cyclopoid copepod abundance in awba Reservoir, Ibadan (2014)
A study was carried out on the effects of physico-chemical parameters on the microscopic cyclopoid copepod abundance in Awba reservoir, University of Ibadan between January and February 2005.McMaster Microscope was used to observe and identify the copepods while a water quality test kit was used to assess the physico- chemical parameters. The results showed a variation in the physico-chemical parameters of the sites with ranges for dissolved oxygen: 21.2mg/l ± 0.85 to 24 mg/l ± 1.71, biochemical oxygen demand (BOD): 10.3 mg/l ±0.57 to 11.2 mg/l ±1.4. Temperature 28.10C±0.23 to 300C ±2.07, pH 7.2±0.13 to 7.5±0.27 and conductivity 304 µS/cm ± 42.7 to 330.5 µS/cm ± 70.3. Diverse taxonomic groups of cyclops were encountered at the four study sites in Awba Reservoir during the sampling period. The dominant groups varied across the sites. For site 1, Tropocyclops mellonbyi was dominant with a Berger-Parker Diversity Index (BPDI) of 92%, for site 2, Tropocyclops mellonbyi, Halicyclops korodiensis; Thermocyclops iwogiensis were present with a BPDI of 72%, 16% and 12%, respectively. For site 3, Tropocyclops mellonbyi and Halicyclops korodiensis were encountered with a BPDI of 88% and 12% for site 4, Ectocyclops ilariensis had a BPDI of 100% as the only cyclop species. The number of taxonomic groups also varied along the sites. The correlation between the physico- chemical parameters and Cyclops abundance at the four study sites was indicative of the effects of ecological factors on the Cyclops and the potential of cyclops to be used as bioindicators of environmental perturbation in the reservoir